Assessment of Knowledge and Estimated Burden of Life Style Diseases in a Rural Community - Suresh K.N.; Mithu Joy; Ruby V.P. (International Journal of Evidence Based Nursing And Practices, 2023)
Although rapid human evolution has brought about advancement, it has also caused several lifestyle ailments. People’s daily routines have drastically changed as a result of emerging technologies, and it paved the way for numerous life style disorders. According to reports, lifestyle diseases are a major cause of increased mortality globally. Our study highlights the prevalence of life style diseases in the rural community and the need for early identification and treatment to reduce the rate of such diseases. A quantitative approach with descriptive method was adopted to achieve the objectives of the study. Data were collected from 2,827 participants residing in Ward 16 of the Mooppainadu panchayat, Wayanad district with a study duration of 4 months from June to October 2022. A survey was conducted by visiting households to enroll participants, utilizing a convenient sampling method. Participants were interviewed using a pre-designed, pre-tested, and semi-structured questionnaire comprising 20 questions. The data collected were entered into an Excel and analyzed using SPSS. This study findings reveals that out of the total 2,827 population, 1,397 (49%) were males and the rest 1430 (51%) were female and among them 968 people (26%) have life style diseases. Out of the 968 people, 360 have hypertension, 256 have Diabetes, 198 have both diabetes and hypertension, 33 were affected with cardiac problems, 65 with respiratory problems, 8 have neurological problems, 44 were affected with gastro problems, and 4 among them have cancer. Moreover, majority of the population 43.5% had poor knowledge, 30.8% had moderate knowledge, and 25.6 % had good knowledge.
Keywords: COPD; Diabetes; Lifestyle diseases; NCDs; hypertension